Economic Burden of Hypertension in the Russian Federation - Yu. A. Balanova (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2020)
The prevalence of hypertension in the Russian Federation (RF) has been growing in recent years, which causes significant socio-economic burden. Aim. To evaluate economic burden of hypertension in the RF in 2016 including direct costs and economic losses caused by decreased labor efficiency. Material and methods. The calculation included the prevalence of hypertension in the RF and the relative risk of hypertension for cardiovascular diseases (CVD) (including stroke and coronary heart disease), chronic obstructive pulmonary disease (COPD), type 2 diabetes mellitus (DM2), cancer of the trachea, bronchi and lungs, breast and prostate. The calculation included Russian statistics on noncommunicable diseases (NCD) for 2016. Statistical analysis – calculations were performed by Microsoft Excel 10.0 Results. Population attributable risk (PAR) of hypertension in mortality from all CVDs was 34%, in morbidity – 30%, including PAR in mortality from coronary heart disease and stroke 38% and 60%, respectively; the same in morbidity – 28% and 14%, respectively. For DM2 PAR in mortality was 1%, in morbidity – 18%. For COPD PAR in morbidity was ≈24%. PARs in morbidity and mortality for lung, bronchi and trachea cancer were ≈12%, for prostate cancer ≈3%, and for breast cancer 6%. Direct medical costs associated with the analyzed NCDs exceeded 84 billion rubles, direct non-medical costs – over 1.5 billion rubles. In the structure of economic burden, the main part was associated with gross domestic product (GDP) losses due to premature mortality due to hypertension. Conclusion. The total economic burden associated with hypertension in 2016 amounted to 869936 million rubles that corresponded to 1% of Russian GDP.